The confidence trick - S. Keen (Australasian Accounting, Business and Finance Journal, 2009)
This article reflects on the role that confidence plays in recovery from a financial crisis. The author reflects on lessons from the past – specifically The Great Crash of 1929 and on the work of economists Keynes and Fisher to apply to our current economic woes. The role of overconfidence in our current crisis is also examined.
Keywords: Keynes; Fisher; confidence; recovery; economy; Australia; overconfidence; kangaroo economics